2011
DOI: 10.1007/s12237-011-9418-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Nutrient Enrichment and Benthic Function: Local Effects and Spatial Patterns

Abstract: Eutrophication-induced changes to benthic faunal activities are problems of significant ecological impact, affecting global nutrient budgets as well as local trophic connections. We address the question of how nitrogen loads to estuarine embayments alter the bioturbation activities of benthic fauna. Specifically, we related local benthic activities to calculated local nitrogen concentrations for 22 northeastern US estuaries. These local nitrogen concentrations were derived from the calculated nitrogen loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Species richness may show a range of responses to stress or resource availability including the humpbacked curve described by the intermediate-disturbance hypothesis, which shows an increase in diversity with increasing stress or resource availability before decreasing again as stress continues to increase (Connell, 1978;Odum, 1985;Dodson et al, 2000;Mittelbach et al, 2001;Hooper et al, 2005;Huston, 2014). This pattern has also been shown for the response to nitrogen loadings in functioning of benthic invertebrate communities, for example in bioturbation rates (Abdelrhman & Cicchetti, 2012). In some cases, nutrient enrichment can increase species richness and productivity through increased survival and recruitment, by making more resources available and mitigating the effects of other stressors such as heavy metal contaminants (Lawes et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Species richness may show a range of responses to stress or resource availability including the humpbacked curve described by the intermediate-disturbance hypothesis, which shows an increase in diversity with increasing stress or resource availability before decreasing again as stress continues to increase (Connell, 1978;Odum, 1985;Dodson et al, 2000;Mittelbach et al, 2001;Hooper et al, 2005;Huston, 2014). This pattern has also been shown for the response to nitrogen loadings in functioning of benthic invertebrate communities, for example in bioturbation rates (Abdelrhman & Cicchetti, 2012). In some cases, nutrient enrichment can increase species richness and productivity through increased survival and recruitment, by making more resources available and mitigating the effects of other stressors such as heavy metal contaminants (Lawes et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…This response was in line with studies that have found nutrient enrichment can lead to increased species richness, greater availability of resources, greater productivity and rates of functioning and increased survival and recruitment in benthic communities (e.g. Borja et al ., 2009 b ; Abdelrhman & Cicchetti, 2012; Krumhansl et al ., 2015; Lawes et al ., 2016). Species richness can respond to disturbance by initially increasing, corresponding to the intermediate disturbance hypothesis (Connell, 1978; Odum, 1985; Dodson et al ., 2000; Mittelbach et al ., 2001; Hooper et al ., 2005; Huston, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation